The impact of antifungals on toll-like receptors - Mihu, Mircea R.; Pattabhi, Rodney; Nosanchuk, Joshua D. (Frontiers in Microbiology, 2014)
Fungi are increasingly recognized as major pathogens in immunocompromised individuals. With the increase in the number of fungal infections each year and the development of resistance to current therapy, new approaches to treatment including stimulation of the immune response in addition to concurrent pharmacotherapy is ongoing. The most common invasive fungal infections are caused by Candida spp., Aspergillus spp., and Cryptococcus spp. Amphotericin B (AmB) has remained the cornerstone of therapy against many fulminant fungal infections but its use is limited by its multitude of side effects. Echinocandins are a newer class of antifungal drugs with activity against Candida spp. and Aspergillus spp. and constitutes an alternative to AmB due to superior patient tolerability and fewer side effects. Due to their oral delivery, azoles continue to be heavily used for simple and complex diseases, such as fluconazole for candidal vaginitis and voriconazole for aspergillosis. The objective of this paper is to present current knowledge regarding the multiple interactions between the broad spectrum antifungals and the innate immune response, primarily focusing on the toll-like receptors.